Fracture and dislocation of a glass intraocular lens optic as a complication of neodymium:YAG laser posterior capsulotomy: Case report and literature review. Issue 10 (October 2015) - Singh, Harmanjit; Kwan, Sarah L.; Tam, Diamond; Mamalis, Nick; MacLean, Kyle; Ahmed, Iqbal Ike K.
Abstract : N/A: An 83‐year‐old man presented with a 1‐year history of blurry vision in his left eye. Bilateral cataract surgery and ciliary sulcus posterior chamber intraocular lens (IOL) implantation had been performed 11 years earlier. The corrected distance visual acuity (CDVA) was 20/60 in the left eye. Slitlamp examination revealed moderate posterior capsule opacification. Neodymium:YAG laser posterior capsulotomy was performed and complicated by IOL fracture and immediate dislocation of optic fragments into the anterior chamber. An IOL exchange was performed, and the damaged IOL was removed in 7 pieces. A 3‐piece acrylic IOL was suture fixated to the posterior iris. Pathologic analysis showed that the damaged IOL was made of glass supported by a polyimide frame. Twelve months after the IOL exchange, the CDVA was 20/60. Financial Disclosure : Dr. Ahmed is a consultant to Alcon Laboratories, Inc., Abbott Medical Optics, Inc., and Bausch & Lomb. Dr. Mamalis is a consultant to Anew Optics, Inc., and Medennium, Inc. No other author has a financial or proprietary interest in any material or method mentioned.